Continuous Tissue Plasminogen Activator Infusion Using a Minimally Invasive Irrigating Catheter for the Treatment of Intraparenchymal Hemorrhage Within the Basal Ganglia: Case Reports. Issue 6 (14th December 2022) - Varela, Samantha; Carrera, Diego; Elazim, Ahmed Abd; Robinson, Myranda B.; Torbey, Michel; Carlson, Andrew P.
Abstract : BACKGROUND AND IMPORTANCE: Intraparenchymal hemorrhage (IPH) is a debilitating and highly morbid type of stroke with limited effective treatment modalities. Minimally invasive evacuation with tissue plasminogen activator (rt-PA) has demonstrated promise for mortality/functional improvements with adequate clot volume reduction. In this study, we report 2 cases of continuous rt-PA infusion using a closed circuit, dual lumen catheter, and irrigation system (IRRAflow) for IPH treatment. CLINICAL PRESENTATION: A 55-year-old man was admitted for acute onset left hemiparesis; he was found to have right basal ganglia IPH. He was treated with continuous rt-PA irrigation using the IRRAflow device, at a rate of 30 mL/h for 119 hours, with a total volume reduction of 87.8 mL and post-treatment volume of 1.2 mL. At 3-month follow-up, he exhibited a modified Rankin score of 4 and improved hemiparesis. A 39-year-old woman was admitted for acute onset left facial droop, left hemianopsia, and left hemiparesis; she was diagnosed with a right basal ganglia IPH. She was treated with drainage and continuous rt-PA irrigation at 30 mL/h for 24 hours, with a total hematoma volume reduction of 41 mL and with a final post-treatment volume of 9.1 mL. At 3-month follow-up, she exhibited a modified Rankin score of 3 with some improvement in left hemiparesis. CONCLUSION: Continuous rt-PA infusion using a minimally invasive catheter with saline irrigation was feasible and resulted in successful volume reduction in 2 patients with IPH. This technique is similar to the Minimally Invasive Surgery Plus rt-PA for Intracerebral Hemorrhage Evacuation (MISTIE) approach but offers the potential advantages of less breaks in the sterile circuit, continuous intracranial pressure monitoring, and may provide more efficient clot lysis compared with intermittent bolusing.